Tabayyun Informasi di Era Media Sosial - Hariyanto, Hariyanto Hariyanto (BINA' AL-UMMAH, 2017)
AbstractSocial media has become a major means of communicating across distances. Various information can be obtained quickly. Broadly speaking, information in social media includes religion, social, political, economic, legal, historical, etc. In the social media user community (medsos) there is a difference in attitude when receiving messages. At least the attitude of the medsos user is divided into five categories; First, do not read the message. Second, just read. Third, read and spread. Fourth; reading but not spreading. Fifth, not reading but spreading.The variability of accessible information requires a "filter" which in this study is called "tabayyun". Tabayyun is an attempt made someone to seek clarity or truth of information. Information that is spread through social media is not all should be trusted and widely disseminated. This is so because the information scattered in social media can be right and wrong (hoaks).Regulations that have been built by the government have not been able to reduce the rapid information hoaks in social media. The existence of the Saracen network is a group of hoax news producers (hoaks) can be interpreted a sign that hoaks messages are spread in social media has been organized / planned a group. In fact, hoaks messages have become industrasi so that the perpetrators more tempted to continue to produce hoaks message. Therefore. In an attempt to counteract the hoax, it is important to look at current realities by referring to the holy texts of the Qur'an. Thus, the authors will examine and explain the contextualisation of Al-Qur'an commentary of Al-Hujurat letter (49) verse 6 in the era of social media which has three ways: First, Tabayyun. Second, ask the expert / media literacy. Third, clarification.Kata Kunci : Tabayyun, Social Media